Foreign direct investment and exports stimulate economic growth? Evidence of equilibrium relationship in Peru - Ciro Eduardo Bazán Navarro; Víctor Josué Álvarez-Quiroz (Economies, 2022)
The purpose of this research is to estimate the dynamic impacts of foreign direct investments (FDI) and exports on economic growth in Peru (1970-2020) using annual series. Starting with the theoretical Mundell-Fleming static model with assumptions, we find that the change in exports does not affect GDP, and the effect of FDI on GDP can be positive or negative depending on the comparison between the slopes of the IS and LM curves. The variables are foreign direct investment net flow (% of GDP), exports of goods and services (% of GDP), and GDP growth rate (%). FDI and exports constitute first-order integrated processes; meanwhile, the GDP growth rate is a stationary process. The Granger causality evidences feedback between GDP and exports and the FDI-led growth hypothesis. Considering the dependent variable GDP growth rate, the autoregressive distributed lag cointegration bound test shows the findings regarding the cointegration consist of positive long-term equilibrium impacts from exports and FDI on GDP. Estimating an error correction model, in the short-term, the FDI explains to GDP and the exports have an insignificant impact on economic growth in Peru. Finally, we conclude that Peru's economic policy path should continue to attract foreign capital to increase FDI.
Keywords: E22; F21; F43; O11; O40; 330; autoregressive distributed lag cointegration bound test; economic growth; exports; foreign direct investment; Granger causality; Mundell-Fleming model